Formulation, optimization, characterization and in-vitro drug release kinetics of atenolol loaded PLGA nanoparticles using 33 factorial design for oral delivery. (August 2016) - Chourasiya, Vibha; Bohrey, Sarvesh; Pandey, Archna
Graphical abstract: Abstract: This work was aimed to formulate the atenolol loaded PLGA nanoparticles through optimizing formulation variables using 3 3 factorial design. FTIR studies were performed to examine the interaction between the excipients used. These nanoparticles were characterized by size, shape, zeta potential, % drug entrapment efficiency, process yield and in-vitro drug release behavior. Different kinetics models were used to analyze the in-vitro drug release data. Preferred formulation showed particle size 192.6 ± 3.5 nm, PDI 0.234 ± 0.008, −32.4 mV zeta potential, drug entrapment efficiency 71.65 ± 1.8% and 78.32 ± 1.1% process yield. TEM results showed that these nanoparticles were spherical in shape and follow the Korsmeyer-Peppas model.